Diversity and dominance of earthworms in relation to abiotic factors in the Southern Mountain Forest of Tarakan Island - Palungana, Chrizt Jensen; Umar, Hardianto S; Nirmala, Adelya Setia; Nugroho, Bimo Aji (Biological Environment and Pollution, 2024)
Forest degradation continues to occur due to the expansion of agricultural land which disrupts its fauna. One of the fauna that faces threats is earthworms, earthworms play an important role as decomposers. This study aims to address the dearth of information on the diversity and dominance of earthworms and to compare their presence in two habitats, agricultural areas, and primary forests in the Gunung Selatan Forest area, Tarakan, and their relationship to abiotic factors. Sampling was conducted on agricultural land and primary forest using hand sorting techniques on plots measuring 30x30 cm, totaling six plots. The results showed that there were two types of earthworms, namely Lumbricus terrestris and Lumbricus rubellus. Researchers found 5 individuals of Lumbricus terrestris and 2 individuals of Lumbricus rubellus on agricultural land, 11 individuals of Lumbricus terrestris, and 7 individuals of Lumbricus rubellus in primary forest. Each worm sample's length and body researchersight varied depending on its location. The study found differences in the number and shape of earthworms living in agricultural land and primary forest habitats in the Gunung Selatan Forest area of Tarakan. More earthworms researchers found in primary forest habitats than in agricultural land. The study's results prove a relationship between abiotic factors and the life of earthworms, based on the measurement of parameters; the higher the temperature, air humidity, light intensity, and soil pH, the fewer worm species are obtained. Researchers anticipate these findings to offer valuable insights for managing and conserving ecosystems.